2019
DOI: 10.1038/s41598-019-53980-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential value of brain magnetic resonance imaging in multiple system atrophy cerebellar phenotype and spinocerebellar ataxias

Abstract: Clinically differentiating multiple system atrophy cerebellar (MSA-C) phenotype and spinocerebellar ataxias (SCAs) is challenging especially in the early stage. We assessed diagnostic value of brain magnetic resonance imaging (MRI) in differentiating MSA-C and SCAs based at different disease stages (<3, 3–7, and >7 years of disease duration). Overall, 186 patients with probable MSA-C and 117 with genetically confirmed SCAs were included. Hot cross bun (HCB) signs and middle cerebellar peduncle (MCP) hyperinten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 33 publications
2
38
0
2
Order By: Relevance
“…Among patients imaged within 2 or 3 years after onset, grade 2 HCB was observed in none of those with SCA3, yielding a high specificity of 100% for distinguishing between MSA-C and SCA3. In line with the results of this study, previous studies that evaluated HCB in MSA-C and SCA including SCA2, SCA3, SCA7, and SCA8, described that grade 2 HCB was not observed in 39 patients with SCA3 within 3 years after onset [16]. In an evaluation of the HCB in adult cerebellar ataxia that included 33 patients with SCA3 (disease duration 6.3 ± 6.0 years), a pontine midline linear hyperintensity was observed 24 (72.7%), but none had the complete cruciform HCB [15].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Among patients imaged within 2 or 3 years after onset, grade 2 HCB was observed in none of those with SCA3, yielding a high specificity of 100% for distinguishing between MSA-C and SCA3. In line with the results of this study, previous studies that evaluated HCB in MSA-C and SCA including SCA2, SCA3, SCA7, and SCA8, described that grade 2 HCB was not observed in 39 patients with SCA3 within 3 years after onset [16]. In an evaluation of the HCB in adult cerebellar ataxia that included 33 patients with SCA3 (disease duration 6.3 ± 6.0 years), a pontine midline linear hyperintensity was observed 24 (72.7%), but none had the complete cruciform HCB [15].…”
Section: Discussionsupporting
confidence: 91%
“…An HCB of either grade 1 or 2 had a high sensitivity of 91.7% in MSA-C within 2 years after disease onset, and a grade 2 HCB had a sensitivity of 54.2% at 2 years and 66.7% at 3 years after disease onset. Our findings suggest that, in a case of progressive cerebellar ataxia, if an HCB is not observed on MRI within 2 years after the onset of cerebellar symptoms, it is unlikely that the diagnosis is MSA-C. A recent study showed that either a vertical or a cruciform hyperintensity was detected in 80.1% (149/186) of the patients with MSA-C within 3 years after onset [16]. This result is consistent with that of this study but had a lower frequency.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…An HCB of either grade 1 or 2 had a high sensitivity of 91.7% in MSA-C within 2 years after disease onset, and a grade 2 HCB had a sensitivity of 54.2% at 2 years and of 66.7% at 3 years after disease onset. Our findings suggest that, in a case of progressive cerebellar ataxia, if an HCB is not observed on MRI by 2 years after onset of cerebellar symptoms, it is unlikely that the diagnosis is MSA-C. A recent study showed that either a vertical or a cruciform hyperintensity was detected in 80.1% (149/186) of the patients with MSA-C within 3 years after onset [16]. This result is consistent with that of this study but had a lower frequency.…”
Section: Discussionmentioning
confidence: 56%